Phenomenological Exploration of the Challenges and Strategies for Implementing the “Entrepreneurship and Production Workshop” Curriculum in Upper Secondary Education: Based on Teachers’ Lived Experiences - Nouri, Parisa; Sheikhi Fini, Ali Akbar; Zeinalipour, Hossein; Samavi, Seyyed Abdolvahab; Sabzeh, Batool (Assessment and Practice in Educational Sciences, 2025)
This qualitative study, employing a phenomenological approach, examined the experiences of upper secondary theoretical school teachers in Tehran regarding the challenges and strategies for implementing the “Entrepreneurship and Production Workshop” curriculum. Data were collected through semi-structured interviews with 17 teachers selected purposefully and continued until theoretical saturation was achieved. The data were analyzed using inductive content analysis. Findings revealed that implementing this course faced significant challenges across five main dimensions: lack of teachers’ specialized and practical competencies in entrepreneurship education; infrastructural, financial, and technological limitations; weaknesses in teacher preparation and professional empowerment systems; misalignment between the textbook content and students’ real needs and environmental changes; and absence of effective linkages between schools, industry, and society. Furthermore, the teachers’ suggested strategies were analyzed at three levels: macro-level policymaking, structural and organizational reforms, and improvement of instructional processes. The results of this study emphasized the necessity for a comprehensive review of policies, content, human resources, and executive mechanisms. They also demonstrated that achieving the goal of fostering entrepreneurial competencies in schools is only possible through structural reforms and the utilization of cross-sectoral capacities.